Responding to Modern Sensibilities: Emma and Edvard Entangled - Berman, Patricia G. (Text Matters: A Journal of Literature, Theory and Culture, 2017)
This article is an edited version of the response paper offered at the conclusion of the symposium, Modern Sensibilities. It ties together themes from the symposium papers, as well as ideas prompted by Mieke Bal’s exhibition, Emma & Edvard: Love in the Time of Loneliness, and her accompanying book, Emma and Edvard Looking Sideways: Loneliness and the Cinematic. It focuses on the anachronistic entanglements among Flaubert’s “Emma,” Munch’s motifs, Mieke Bal and Michelle Williams Gamaker’s Madame B, the Munch Museum’s architecture and exhibition scenography, and the exhibition viewer.